Research design in social work : qualitative, quantitative & mixed methods - Campbell, Anne; Taylor, Brian J.; McGlade, Anne (Los Angeles, CA : SAGE Publications, Inc., 2017)
Social work research often focuses on qualitative designs and many students believe that the quantitative research pathway is either too complicated or is beyond their grasp. This book outlines how social work students can undertake a research project from either a qualitative, quantitative or mixed methodological approach. The authors introduce key concepts in an accessible and structured manner and go on to demonstrate each of the approaches from inception of research idea, to realisation of methodological approach, to research process, to data analysis and conclusion.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Social service -- Research -- Methodology